River Basin Management in the Twenty-First Century: Understanding People and Place - Squires, V. R. (Victor R.); Milner, Hugh M.; Daniell, Katherine A. (CRC Press, 2014)
Worldwide development of agriculture and industry creates burgeoning demands on natural resources. Management of the rivers and the surrounding landscape is one of the important tasks for today and for the foreseeable future. Lessons learned from centuries of management (and mismanagement) have been distilled into principles and practices which for